STUDI LITERATUR TENTANG KEPERCAYAAN DIRI SISWA REMAJA - lestari, Sri; Saam, Zulfan; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrak: This research was conducted to determine the basic concepts and theories, factors and efforts to overcome the Adolescent Student Confidence. The type of research used is literature study. The instrument used in this research is a combination of national journals and international journals. Data analysis in this study used qualitative. The results showed that self-confidence is a personal characteristic of a person in which there is self-confidence and ability and is able to develop and cultivate himself as a person who is able to cope with a problem with the best situation. And there are also various theories found in the research results from the research results that can be used as discussing one of the problem formulations of the results of the research. The factors that influence are internal and external factors that exist in adolescent students. So that efforts can be made by providing Self-Intruction technique group guidance services, student activity techniques in class, Ex Post Facto approach, random sampling technique, Open-ended approach, closed-ended approach, application of the jigsaw learning method, application of the STAD learning method, approach social support groups, the application of group guidance to symbolic modeling techniques.Key Words: Literature study, self-confidence, adolescent students